Meteorological Drought Assessment in Wonogiri District - Karlina Karlina (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2016)
Drought is one of natural disaster occurrences that affect many life aspects such as agricultural and economy. Drought is one of hazard that affected by extreme condition due to climate change. Wonogiri is one of districts in Indonesia that has a high risk of meteorological drought. This area tends to have less rainfall than other areas that make the condition drier. This study is aimed to provide some information required in determining the drought disaster mitigation through analysis of the drought characteristics, for both historical and future condition. For the historical condition analysis, the input is 12 years of daily rainfall recorded data from 1990 to 2001 in 15 rain gauges. In case of the future assessment, the meteorological drought was analyzed by using Effective Drought Index (EDI) and Standardized Precipitation Index (SPI) methods. Input data for the future assessment is 90 years of daily rainfall which was generated by using climate model HadCM3 scenario A2 and B2. The future data prediction was done by using Automated Statistical Downscaling software. Statistical criteria i.e. Root Mean Square Error (RMSE), regression coefficient and standard deviation were used for testing the model accuracy. The drought coefficient obtained from the analysis using EDI and SPI then was applied to draw drought risk map using GIS software in Wonogiri District for historical and future condition. The results show that for the historical condition, the most severe drought occurred in 1997-1998. This extreme condition related to ENSO phenomenon that happened in this area. Compared with the historical condition, the number of future drought event in 2080 period is less than the historical one. This result agree with the rainfall prediction. The generated rainfall for both scenarios are increase from existing period to 2080’s.